PELAKSANAAN EDUKASI PENCEGAHAN STUNTING PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS LUBUK BUAYA KOTA PADANG - Aninora, Novia Rita; Satria, Epi (Jurusan Kebidanan Poltekkes Kemenkes Riau, 2021)
Adequate nutritional intake is needed by pregnant women, these nutritional needs are needed for pregnant women to be able to provide good nutrition to the fetus for fetal growth and development in the womb. Pregnant mothers class activities are a means to study groups about health for pregnant women in the form of face to face. The form of community service activities carried out is the implementation of counseling about balanced nutrition for pregnant women and the provision of supplementary food for pregnant women in the pregnant mothers class at Nanggalo Public Health Center in Padang in February 5, 2019. The purpose of this activity is so that all pregnant women who are in the class of pregnant women Nanggalo Community Health Center knows about balanced nutrition that must be consumed during pregnancy. The results of this community service are all pregnant women who are in the class of pregnant women Nanggalo Health Center knows about the benefits and balanced nutrition that must be consumed during pregnancy. Pregnant women with good nutritional knowledge are expected to be able to choose foods that are of good nutritional value and balanced for themselves, the fetus and family.Keywords: Knowledge, Nutrition for Pregnant Women